The New Game with the Old Rules: Boundary Determination Under MMP - Beever, Graham (Victoria University of Wellington Law Review, 2003)
In 1996, New Zealand experienced its first election under MMP, a system of proportional representation. MMP had been recommended ten years earlier by the Royal Commission on the Electoral System. However, some of the details surrounding the operation of the new system differ significantly from the original recommendations of the Royal Commission. In relation to the determination of electoral boundaries, an issue of considerable importance under the previous First Past the Post system but of diminished significance under MMP, there are two particularly important differences. One of these is the retention of two political representatives on the Representation Commission, the body responsible for determining electoral boundaries. The other is the retention of the electoral tolerance at the relatively low level of five percent. The electoral tolerance is the quantity that determines the acceptable variation in population between electorates. The paper concludes that the political representatives should be removed from the Representation Commission, and that the tolerance should be raised to ten percent, as originally envisaged by the Royal Commission. The entrenched status of these provisions makes reform especially challenging. However, there is evidence to suggest, at least in relation to the tolerance level, that cross-party consensus may be able to be achieved.